Effect of garlic juice on quality changes of oyster (Crassostrea belcheri) meat during chilled storage - Bunyarat Bunruk; Sunisa Siripongvutikorn; Pornpong Sutthirak (Syiah Kuala University, 2012)
Surat-thani oyster, a big and thin-shell bivalve mollusks, has been registered as Geographical Indicators, GI, as its good taste and delicacy as well as nutritious. Eaten style is raw then there is high risk to face with some disease as oyster is filter feeder. Physical, chemical, microbiological and sensory qualities after the oyster meat treated with the garlic juice at 0, 2 and 3 ml, respectively were monitored. Though initial pH of the control, untreated with garlic juice, was higher compared with the sample treated with 3 ml garlic juice, pH of it (control) was significantly lower (p0.05) than the sample treated with the juice during storage. The total volatile base (TVB), chemical quality, values of all samples increased when increased storage time but not over 35 mg/100 g sample. During chilled storage, lactic acid content of all samples increased as storage time increased but the sample treated with the juice was higher compared with the control. A thiobarbituric acid reactive substance (TBARS), rancidity indicator, of the control was higher than the sample treated with the juice. K-value (%) of all oyster meats increased however; the lowest value was found in the control at end of storage, 12 days. Ammonia content of all samplesslightly increased during storage. Lactic acid content of the treated sample was higher than control after stored for 12 days. Both mesophilic and lactic acid bacteria of all samples tended to increase during storage. Mesophilic ofcontrol, sample-injected with garlic juice 2 ml and 3 ml increased from 3.89± 0.04 to 6.2±0.04, 3.62±0.18 to 5.89±0.06 and 3.57±0.02 to 6.04±0.10 log CFU/g, respectively at end of storage. Lactic acid bacteria of control andsample-injected with garlic juice 2 ml and 3 ml changed from 1.71±0.02 to 2.94±0.04, 1.79±0.09 to 4.63±0.08 and 1.84±0.04 to 4.82±0.10 log CFU/g, respectively. However, psychrophilic, coliforms, fecal coliforms, Escherichia coli,Staphylococcus aureus, Salmonella spp. and Vibrio spp. were low throughout the storage. Consumer acceptability scores were higher than borderline (5) at the end of the storage